5 GHz microstrip patch antenna from pineapple leaf-based substrate for environmentally sustainable wireless communication - Azahani Natasha, Azman; Giamasrow, Rudraa Devi; Nurfarhana, Mustafa; Nurhafizah, Abu Talip Yusof; Norazwina, Zainol; Izzeldin Ibrahim, Mohamed Abdelaziz; Ayib Rosdi, Zainun; Mohamad Shaiful, Abdul Karim (Semarak Ilmu Publishing, 2025)
Pineapples generate approximately 75% waste, each with its unique characteristics. Pineapple leaves have the potential to be utilized in the development of new fibres or raw materials. This study aims to present the design of a microstrip patch antenna that utilizes a pineapple leaf substrate to achieve a 5 GHz frequency resonant. The antenna design was simulated using CST software. The manufacturing process of the pineapple leaf substrate involves boiling, drying, blending, filtering, and mixing composite compositions. The dielectric permittivity at a frequency of G-band was determined using the waveguide technique, revealing an outstanding permittivity of 5.03 at 5 GHz. Subsequently, a microstrip patch antenna was fabricated and characterized to validate the concept. The results demonstrate an acceptable agreement between the simulation and the fabricated substrate at 5 GHz in term of return loss.